SOLID WASTE MANAGEMENT IN THE MUNICIPAL MARKET OF CAUCAIA, CEARÁ - Kelly Sousa Rocha, Alana; Arruda dos Santos, Robson; Jeferson Sampaio Diogo, Ivan (Journal of Interdisciplinary Debates, 2021)
Since Brazil is one of the countries which generate more waste in the world and that organic waste represents more than half of this amount, this article aimed to evaluate the life cycle of solid waste in the City Market of Caucaia / CE, carrying out a study with a qualitative and quantitative approach, a descriptive nature and a bibliographic and documentary basis. Using two questionnaires, workes were interviewed, totaling 10 individuals. These individuals were asked about the generation, collection and destination of the waste produced. To understand the management of waste produced in the market, it was decided to interview the city hall technician responsible for the area. Most marketers deposit their waste in the open, do not know the final destination or ways of treating this waste and do not have access to selective collection. More than half of the waste produced has organic origin, however, there are wastes that need specific destination, such as batteries and electronics. Waste management is not very efficient and the city has no strategies. The results obtained show that the management and management of waste from Caucaia / CE still need to undergo some changes, mainly in relation to the destination and treatment of these, especially organic ones.